Milt-to-egg ratio in artificial fertilization of Clarias macrocephalus (Gunther) using salmon gonadotropin-releasing hormone analogue and domperidone - Tambasen, Ma. Victoria P. (College of Fisheries, University of the Philippines in the Visayas, 1993)
The optimum milt-to-egg insemination ratio was ivestigated using milt extracted from Ovaprim (0.02 ug salmon gonadotropin-releasing hormon analogue + 10 ug domperidone /ul)-treated Asian freshwater catfish, clarias macrocephalus (Gunther).Milt production was measured 12, 24, and 48 h after a single intramuscular injection of 0, 0.5, 1, and 2 ulOvaprim/g BW Experiment 1). Mean milt procuction (5.84 ul/g BW) peaked at 24 h after incjection of 2ulOvaprim/g BW (0.04 ugSGnRHa + 20 ug DOM/g BW), while mean sperm density significantly decreased to 2.55 x 106 spermatozoa/ul. Fertilization, hatching, and larval survival rates werenot significantly different when milt from treated and untreated males inseminated I g of ovulated eggs. Various aliquots (2, 5, 5, 10 g) of ovulated eggs were also inseminated by different volumes (2, 5, 10, 25, 50, 100, 200 ul) of diluted milt extracted 24 h post-injection of2 ulOvaprim/g BW (Experiment 2). Fertilization was significantly affected by the volume of diluted milt (1:3.5 in 0.9% NaC1) used, but not by the quantity of eggs inseminated. Hatching rates (13-50%) were variable, although more eggs hatched following insemination by moremilt. Survival of larvae (60-79%) did not significantly differ when aliquots of ovulated eggs were fertilized by various volumes of diluted milt. Fertilization (70%) and hatching (41-46%) rates using data pooled from 2, 2.5, and 10 g aliquot egg samples were consistently high wheninseminated by 25 and 50 ul milt, indicating that the optimum insemination ratio in 25.50 ul milt to 10 g egg, or approximately 4-8 x 103 spermatozoa/egg. A 100 g male catfish injected 2 ulOvaprim/g BW can therefore produce 5.84 ul milt/g BW, which is capable of fertilizing 286572 g eggs from 13-26 females. This study demonstrated an effective means of stimulating milt production by Ovaprim treatment and a practical method of artificial fertilization of catfish which maximized the use of limited quantities of extracted milt.-